Moving from Youth Migration to Mobility: Spatial Distinction and the Evolution of the Mobilities/Transitions Nexus - Cairns, D. ((Re)searching for a Nexus: Contemporary Youth between Mobility and Migration, 2024)
This discussion explores the significance of youth migration and mobility to career development, drawing on relevant theoretical precedents and empirical evidence. The first part of the talk focuses on conceptual issues, including the idea that spatial and social mobility are linked, with time spent abroad providing a means of generating distinction within transitions to the labour market. This belief, and other ideas associated with Bourdieu including mobility capital and habitus, helps to explain how and why certain individuals become spatially mobile in their careers, also providing a rationale for the multiplication and diversification of mobility opportunities, reflected in the emergence of a new mobilities paradigm from Urry and colleagues. The second part of the talk looks at the evolution of mobilities/transitions nexus, using evidence from biographical interviews conducted with 100 researchers in Portugal, conducted during 2022 and 2023. Taking a cross-sectional view of this evidence, it is possible to look at how the efficacy of youth migration and mobility has changed for researchers, starting with examples of the exceptional success enjoyed by individuals who migrated at a time when such practices were uncommon and capable of generating distinction, continuing with exploration of the experiences of people who moved after the parameters of the mobilities/transitions nexus widened, making distinction via spatial circulation harder to attain, bringing into question the value of mobility capital for young people seeking to initiate professional careers.